Destination New Zealand: A history of the Afrikaans Christian Church of New Zealand - Merwe, Johan M. Van der (HTS teologiese studies, 2015)
The advent of democratic change in South Africa in the 1990s led to an exodus of many White Afrikaans-speaking Christians from South Africa. They settled all over the world. One of the countries of choice was New Zealand. A group of these emigrants came together in Auckland, New Zealand, in 1998 and founded an Afrikaans church. The Church grew from one congregation to a denomination that currently has nine congregations. This article describes the history of the Afrikaanse Christen Kerk van Nieu-Seeland [Afrikaans Christian Church of New Zealand]. It focuses on the founding, growth, Church Order, ministry and challenges of the Church. The sources for this article are primary documents collected by the author in New Zealand.